Diretrizes para adequação à construção sustentável: estudo para aplicação em uma instituição de ensino - Kalichtzuk, Giovanna Palmigiano [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Since Mankind has begun to settle and form societies, cities, he has been affected by the consequences it's bad use of environmental resources has led to happen;; examples as water pollution, soil deterioration. But what in fact led to a alarming situation was what started in the 18th century, the industrial revolution, which stimulated population growth, mass production and consumption (this one more and more into global culture). It is not that economic growth, profit, are not really important for a society disenrollment, but what the cost of its life quality this same society has to pay in the future. Global population continues to grow, just as industries and urban areas, and causes for example heat islands to get warmer, phenomenon this that occurs in cities agglomerations, this which haven't the structure or are planned for such population. Within the solutions that come up, to at least minimize the impacts, is to give more efficiency to constructions as to being less threatening to the environment, such as less energy consumption, water reuse. For so the industry is creating technologies that are capable to issue or at least optimize the buildings function to as a more sustainable one. This study and the disenrollment of the Project has as main intent to research the alternatives and technologies that are applicable to Existing buildings, as well as it's socioeconomic and Environmental efficient points, and that can be put in practice in a school. This research is based on a specific certification for its international recognition, as well as the fact that embraces different aspects sustainability, and also previous studies on alternatives and sustainable technologies. The certification which was used as a model has it's adaptation for hospitals, commercial centers, homes, and so on as to create different scenarios as for what a construction is used for. The choice was to use the model for schools

Desde que o homem começou a se estabelecer em uma área específica e a se agrupar em vilas/burgos/cidades, tem-se observado a degradação dos espaços ocupados. Mas, com a revolução industrial, a qual estimulou o crescimento populacional, revolução verde, produção e consumo, houve um aumento significativo na degradação do meio ambiente. Por mais que o desenvolvimento econômico, o lucro, tenha grande importância no desenvolvimento de uma sociedade, o prejuízo e a deterioração causada por este modelo com descarte desenfreado sem consciência atinge diretamente a qualidade de vida e o futuro desta mesma sociedade. A população mundial continua a crescer, assim como as industrias e áreas urbanas, causando assim maiores e mais fortes ilhas de calor, fenômeno que ocorre em grandes centros de urbanização, trazendo problemas nas estruturas não planejadas para tamanha população. Dentre as soluções que surgem e são propostas, para minimizar os impactos, é a maior eficiência para construções serem menos ameaçadoras ao meio ambiente, consumindo menos energia, reutilizando e tratando água. Para isso, cada vez mais são desenvolvidas tecnologias capazes de sanar, ou pelo menos otimizar o funcionamento em direção da sustentabilidade. A pesquisa e o desenvolvimento deste projeto têm como objetivo pesquisar as alternativas e tecnologias de construção sustentáveis existentes, sua eficácia econômica e socioambiental e que podem ser aplicadas em uma instituição de ensino. O trabalho foi baseado em uma certificação em especifico por abranger diferentes aspectos da sustentabilidade além do maior reconhecimento internacional, e em estudos previamente feitos ao redor do tema de tecnologias alternativas e sustentáveis. A certificação que foi usada como base possui adaptações para hospitais, centros comercias, residências, entre outros, de forma a criar diferentes cenários para uso de uma construção. A escolha foi...
Keywords: Desenvolvimento sustentável; Construção civil; Certificação; Construção sustentável; Escolas; Degradação ambiental; Impacto ambiental; Sustentabilidade